Vespas Parasitoides (Hymenoptera: Ichneumonoidea, Braconidae) do Cerrado do Brasil Central - Gomes, Julia Gibertoni (Universidade Federal de São Carlos, 2021)
There is still little knowledge about invertebrates in the Brazilian Cerrado, the most diverse tropical savanna with high endemism of plant and animal species. This work aimed to understand the parasitoid wasps of the Braconidae family of this biome, that are specialized in the use of other insects, mostly herbivores, for the development of their offspring. The study was carried out on the Chapada dos Veadeiros (PNCV) and Grande Sertão Veredas (PNGSV) National Parks, located in the Central Brazilian Cerrado, where we estimated the diversity, richness and abundance of the Braconidae fauna, also verifying the differences that occurred in the cerrado that had suffered with forest fires with the intact cerrado of the Chapada dos Veadeiros National Park. A total of 69 genera and 21 subfamilies were sampled in the PNGSV, with the subfamilies Doryctinae, Microgastrinae and Braconinae being the most abundant. In the intact PNCV there were 68 genera in 21 subfamilies and in the burned PNCV 72 genera were sampled in 21 subfamilies, being the subfamilies with greater abundance Microgastrinae and Homolobinae in the PNCV and Braconinae in the burned PNC. The beta diversity between PNCV and PNGSV varied 15%, and 30% between the intact and burned cerrados of the PNCV. The burned PNCV showed great heterogeneity between the points. New species were found in both parks, and a new genus from the subfamily Hormiinae has been described in PNGSV. The results of this work are of great relevance for the knowledge of the fauna of parasitoids in the Cerrado and for their biological interactions.
Parasitoid Wasps (Hymenoptera: Ichneumonoidea, Braconidae) from the Cerrado of Central Brazil
Keywords: Braconidae; Biodiversidade; Unidade de conservação; Incêndios florestais; Forest fires; Biodiversity; Conservation units; CIENCIAS BIOLOGICAS::ECOLOGIA